Development of IPA about Digital-Based Hydroponic Cultivation as Students' Life Skills - Mar'atus Solicha; Rufi'i Rufi'i; Yoso Wiyarno (EDUTEC : Journal of Education And Technology, 2021)
A reasonable nine-year program requires the school to equip students with life skills so that after graduation students have the ability to live independently. In the learning process of science teachers at SMP Negeri 3 Waru guided by textbooks published by the Ministry of National Education and non-textbooks published by MGMP IPA Sidoarjo Regency, which for modern plant cultivation techniques materials are less interesting for students to learn, due to less interactive learning procedures and applied materials about plant cultivation techniques are less touching towards process skills or practicum, and less supported by images that attract students, especially those that are appropriate for online learning during the pandemic. To solve the above problems, the author makes science teaching materials about digital-based hydroponic plant cultivation techniques that contain interesting materials and various process skills that train students' independence and improve students' understanding of plant cultivation techniques so that it is expected to improve student achievement. Technical data analysis used is Qualitative Discriptis Analysis and Descriptive Percentage Analysis used to process data obtained through questionnaires. The results of this teaching material are validated by material experts and design experts as well as small group tests. The results of the presentation of the achievement rate of the Material experts by 100%, are in the very good category. Of the Design Experts by 92.2%, it is in the category of excellent. Media experts 86.1% Then from the limited group test got a score of 80% large group test of 83.3% while from peers of 86%. Furthermore, the overall flat score so that the teaching materials in the category are good and worthy to be used in science learning.